Patriarchy and the cycle of violence: deconstructing the normalization of violence against women and children in Nagekeo - Mite, Petrus Selestinus (The International Journal of Politics and Sociology Research, 2025)
Cases of violence against children and women are one of the complex and certainly urgent social issues, especially for regions or regions with strong patriarchal social structures. Violence against women and children is not only influenced by patriarchal structures, but is also reinforced by cycles of normalization that perpetuate the practice as part of cultural "normality." This research aims to deconstruct how patriarchal norms work in shaping people's perceptions of violence, analyze the mechanisms of the cycle of violence (reproduction, justification, and impunity), and identify gaps in culture-based interventions to break the chain of violence. A qualitative approach with a content analysis approach through violence case data from the Nagekeo Village Community Empowerment Office (PMD) and content analysis of local media news and previous studies. The things that can be used as novelties in this paper are to provide new knowledge about how patriarchal norms are transforming or persisting in the current era, as well as their implications for violence against women in the local context, especially the Nagekeo-NTT Society. The process and way to find out how patriarchal culture works is to study case data collected by the Village Community Empowerment Office, especially in the field of women and child empowerment. The analysis of the data proves that the number of violence per quarter of the last year tends to be stable and there is a significant increase. These conditions want to strengthen the basic thesis that there is a kind of habit that is considered normal if violence is committed against children and women. Even in terms of awareness, there are people who have dared to report these cases to the relevant agencies or NGOs that handle them.